2019
DOI: 10.1016/j.jaci.2019.07.030
|View full text |Cite
|
Sign up to set email alerts
|

Long-term sublingual immunotherapy for peanut allergy in children: Clinical and immunologic evidence of desensitization

Abstract: Background: Peanut sublingual immunotherapy (SLIT) for 1 year has been shown to induce modest clinical desensitization in allergic children. Studies of oral immunotherapy, epicutaneous immunotherapy, and SLIT have suggested additional benefit with extended treatment. Objective: We sought to investigate the safety, clinical effectiveness, and immunologic changes with long-term SLIT in children with peanut allergy. Methods: Children with peanut allergy aged 1 to 11 years underwent extended maintenance SLIT with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
86
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(87 citation statements)
references
References 25 publications
0
86
0
1
Order By: Relevance
“…suggested improved efficacy with long-term treatment (3-5 years). 129 • Diets containing baked milk or eggs: Mainly for milk and egg allergic patient who can tolerate the baked form of the food (although, some approaches also introduce baked milk in small amounts to baked-milk reactive patients 130 ). It is currently unclear whether consumption of baked food products can accelerate the development of tolerance to unbaked forms of the food (i.e., liquid milk, raw egg).…”
Section: Criteria Data Collected From the Literature Milieu And Consmentioning
confidence: 99%
“…suggested improved efficacy with long-term treatment (3-5 years). 129 • Diets containing baked milk or eggs: Mainly for milk and egg allergic patient who can tolerate the baked form of the food (although, some approaches also introduce baked milk in small amounts to baked-milk reactive patients 130 ). It is currently unclear whether consumption of baked food products can accelerate the development of tolerance to unbaked forms of the food (i.e., liquid milk, raw egg).…”
Section: Criteria Data Collected From the Literature Milieu And Consmentioning
confidence: 99%
“…Recently, children with peanut allergy aged 1 to 11 years underwent extended maintenance SLIT with 2 mg/day peanut protein for up to 5 years [37]. Subjects with peanut skin test wheals of less than 5 mm and peanut-specific IgE levels of less than 15 kU/L were allowed to discontinue therapy early.…”
Section: Sublingual Immunotherapymentioning
confidence: 99%
“…SLIT was assessed through a double-blind, placebo-controlled food challenge with up to 5000 mg of peanut protein after completion of SLIT dosing. Results showed that extended-therapy peanut SLIT provided clinically meaningful desensitization in 67% of children with peanut allergy that was balanced with ease of administration and a favourable safety profile [37].…”
Section: Sublingual Immunotherapymentioning
confidence: 99%
“…With the discovery of IgE in the 1960s, measurements of IgE have been a first step in diagnosis for atopic diseases. Both allergen-specific IgE (sIgE) and total IgE levels increase during the initial stages of AIT and subsequently decrease, 229 however, decreases may not accompany a positive clinical outcome. 230 Numerous studies indicate IgG1 and IgG4 levels increase with therapy but do not always differentiate between responders and non-responders.…”
Section: Specific Ige and Iggmentioning
confidence: 99%